THE USE OF GAMIFICATION TO MOTIVATE STUDENTS IN LEARNING ENGLISH - Ayu, Sindi Putri; Dollah, Syarifuddin; G, Hasriani (Universitas Negeri Makassar, 2025)
This study focuses on the issue of students' lack of motivation to learn English and how the use of gamification as an approach to enhance motivation. The aim of this research was to determine whether or not the use of gamification through platforms such as Kahoot and Quizizz can motivate students in English language learning. The method employed was descriptive qualitative, involving observations and interviews with students ninth grades in three classes of SMP Kartika XX-2. Nine students became the source persons to be interviewed about their opinions on gamification. The results indicate that students feel more motivated after using these gamification tools in the learning process. The conclusion of this research states that gamification can be an effective strategy for increasing student motivation in learning English.